Adherence to Human Colon Cells by Multidrug Resistant Enterobacterales Strains Isolated From Solid Organ Transplant Recipients With a Focus on Citrobacter freundii - Ramos-Vivas, José; Chapartegui-González, Itziar; Fernández-Martínez, Marta; González-Rico, Claudia; Barrett, John; Fortún, Jesús; Escudero, Rosa; Marco, Francesc; Linares, Laura; Nieto, Javier; Aranzamendi, Maitane; Muñoz, Patricia; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Enterobacteria species are common causes of hospital-acquired infections, which are associated with high morbidity and mortality rates. Immunocompromised patients such as solid organ transplant (SOT) recipients are especially at risk because they are frequently exposed to antibiotics in the course of their treatments. In this work, we used a collection of 106 Escherichia coli, 78 Klebsiella pneumoniae, 25 Enterobacter spp., and 24 Citrobacter spp. multidrug resistant strains isolated from transplant patients (hepatic, renal or renal/pancreatic) in order to examine their ability to adhere in vitro to HT-29 human colon cells, and to determine if some adhesive characteristics are associated with prevalence and persistence of these strains. A total of 33 E. coli (31%), 21 K. pneumoniae (27%), 7 Enterobacter spp. (28%), and 5 Citrobacter spp. (21%), adhered to the colon epithelial cells. Two main adherence patterns were observed in the four species analyzed, diffuse adherence, and aggregative adherence. Under transmission electronic microscopy (TEM), most bacteria lacked visible fimbria on their surface, despite their strong adherence to epithelial cells. None of the strains studied was able to induce any cytotoxic effect on HT-29 cells although some of them strongly colonizing both cells and glass coverslips at high density. Some of the strains failed to adhere to the epithelial cells but adhered strongly to the cover-slide, which shows that microscopy studies are mandatory to elucidate the adherence of bacteria to epithelial cells in vitro, and that quantitative assays using colony forming unit (CFUs) counting need to be supplemented with pictures to determine definitively if a bacterial strain adheres or not to animal cells in vitro. We report here, for the first time, the aggregative adherence pattern of two multidrug resistant (MDR) Citrobacter freundii strains isolated from human patients; importantly, biofilm formation in Citrobacter is totally dependent on the temperature; strong biofilms were formed at room temperature (RT) but not at 37°C, which can play an important role in the colonization of hospital surfaces. In conclusion, our results show that there is a great variety of adhesion phenotypes in multidrug-resistant strains that colonize transplanted patients.